GENETIC AND PHYTOCHEMICAL VARIATION IN PLANTAGO MAJOR - Zubair, M. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
Leaves of the common weed Plantago major (common plantain) have been used as a wound healing remedy in almost all parts of the world, and in the treatment of a number of other diseases in folk medicine. The biological activities of P. major leaves are wound healing, anti-inflammatory, analgesic, antioxidant, weakly antibiotic, immuno-modulating and anti-ulcerogenic. The aim of study is to develop: 1. Plantago major, well-known from folk medicine, into a modern medicinal herb, 2. Optimize organic cultivation procedures to produce leaf extracts for use in a superior, biologically active wound dressing. DNA analyses (RAPD) will be conducted for determining genetic variation among populations and for checking homogeneity in offspring from selected mother plants. Chemical analyses (HPLC and mass chromatography) will be performed in order to study different polyphenolic compounds (flavonoids, phenylpropanoid glycosides and iridoids) that are likely to be involvd in the wound-healing ability of P. major. Greenhouse cultvation experiments will be undertaken to check the effects of different levels of light supplementation, heating and fertilization.